Strategies in preflight for an optimal Yurchenko layout vault - Koh, M.; Jennings, L. (Journal of Biomechanics, 2007)
An optimal Yurchenko layout vault of an elite female gymnast was identified by Koh et al. [2003. A predicted optimal performance of the Yurchenko layout vault in women's artistic gymnastics. Journal of Applied Biomechanics 19, 187-204] to require a combination of an increased body angle at horse contact and increased angular momentum for postflight than was recorded experimentally. However, the individual effect of each of these variables to producing the optimal vault is not known. The purpose of the study was to determine an appropriate strategy to teaching the optimal Yurchenko layout vault. Separate optimisations were carried out to investigate how each of these variables would change in order to produce the optimal vault identified by Koh et al. (2003). A combined optimal parameter selection and optimal control approach was used. The results suggest that when the body angle of attack at horse impact was kept low, pre-flight angular momentum had to be increased, with further gains during horse impact, to produce an optimal vault. This strategy of increasing solely the level of angular momentum needed for optimum postflight may not be attainable realistically. On the other hand, employing a larger body angle of attack required an increase in angular momentum during impact but which was attainable. Both optimisations show that increasing the vertical CM horse takeoff velocity is essential for postflight height and distance. The strategy to enhance performance should thus focus on maintaining an appropriate CM pre-flight velocity, a high level of angular momentum during pre-flight and to contact the horse with a large body angle of attack.